PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN FISIK (STUDI TENTANG MUSYAWARAH PERENCANAAN PEMBANGUNAN) DI DESA TANGKURA KECAMATAN POSO PESISIR SELATAN KABUPATEN POSO - Mayusa, Askar (Katalogis, 2018)
This research aims to determine community participation in physical development through the Development Planning Consultation and the role of the Village Consultative Board in Increasing community participation in physical development through the Development Planning Consultation in Tangkura Village, South Coastal Poso District, Poso Regency. This researchwas descriptive qualitative method with purposive determination of informants. The data was taken through primary and secondary data. The Â technique of collecting data was done through observation, interviews, and documentation. The data analysis technique used refers to Miles and Huberman's theory, namely data collection, data reduction, data presentation, and verification and conclusion. To find out the involvement of community in physical development through Development Planning Consultation in Tangkura Village, Abe (2002) used the theory of planning stages, namely participant identification, village problems identification, priority problem analysis, objective analysis, choosing objectives, analysis of strengths and weaknesses, and formulating program results. Then to find out the level of community participation in the planning stage the eight steps of participation theory ware used according to Arstein (2002). The results show that community participation in physical development through the Development Planning Consultation in Tangkura Village, South Coastal Poso District, Poso Regency is at the level of false participation (tokenism). Community involvement in providing information is only inviting interest and legitimacy from the community and reducting public unrest. The role of The Village Consultative Board to increase community participation in physical development through Development Planning Consultation was not optimal. The Village Consultative Board does not conduct aspiration screening other than through the Village Consultation. The presence of the Village Consultative Board in Development Planning Consultation is only as a resource and ratification of the results of the program formulation, so that the role of the Village Consultative Board is categorized in the level of apparent participation (tokenism).